limx→0 (1−cos⁡2x)sin⁡5xx2sin⁡3x equals

limx0(1cos2x)sin5xx2sin3x equals

  1. A

    10/3

  2. B

    3/10

  3. C

    6/5

  4. D

    5/6

    Register to Get Free Mock Test and Study Material

    +91

    Verify OTP Code (required)

    I agree to the terms and conditions and privacy policy.

    Solution:

    We have,

    limx0(1cos2x)sin5xx2sin3x=limx01cos2xx2limx0sin5xsin3x=limx02sinxx2limx0sin5x5x3xsin3x5x3x=2×53=103

    Chat on WhatsApp Call Infinity Learn

      Register to Get Free Mock Test and Study Material

      +91

      Verify OTP Code (required)

      I agree to the terms and conditions and privacy policy.